1983
DOI: 10.1002/bjs.1800700904
|View full text |Cite
|
Sign up to set email alerts
|

The influence of disease at the margin of resection on the outcome of Crohn's disease

Abstract: Sixty-seven patients with Crohn's disease undergoing 81 resections followed by a restorative procedure were reviewed to evaluate the influence of microscopic disease at the margin of resection on the recurrence rate. The average follow-up after resection was 5.6 +/- 2.8 years. The resectional margins were classified into three groups depending on the microscopic appearance of the most involved margin. Recurrent disease developed in 36 per cent of the resections without microscopic evidence of Crohn's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(29 citation statements)
references
References 16 publications
1
24
0
4
Order By: Relevance
“…Our study shows that the presence of inflammatory cells at the resected margins was not associated with an increased risk for a second operation. Moreover, our findings support other reports showing that the outcome of the post-operative course was not associated with the margin length from transected ends of any specimen to the areas of inflammation [22,23,24,25,26,27]. Therefore, our observations support the notion that aggressive surgical interventions with the intention to leave a ‘free’ margin should be avoided.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that the presence of inflammatory cells at the resected margins was not associated with an increased risk for a second operation. Moreover, our findings support other reports showing that the outcome of the post-operative course was not associated with the margin length from transected ends of any specimen to the areas of inflammation [22,23,24,25,26,27]. Therefore, our observations support the notion that aggressive surgical interventions with the intention to leave a ‘free’ margin should be avoided.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have emphasized the relation ship between recurrence rate and involvement of resec tion margin [2, 5, 13, 21] recommending radical resec tions regardless of the risk of short-bowel syndrome. No evidence of the aforementioned relation was found by other authors [1, 8,10,17,19], who therefore advocate limited resection.…”
Section: Discussionmentioning
confidence: 88%
“…Nowadays controversy still arises over how much bowel has to be resected. Certain authors claim that long-bowel resection with negative margins on frozen section minimizes the recurrence rate despite the in creased risk of short-bowel syndrome, since many pa tients often require further resection [2,5], Others limit the length of bowel resection to the macroscopic appear ance [1,10]. As a result of the ongoing controversy, the aim of this study is to evaluate, in a series of 87 consec utive patients, the influence of involvement of resection margins on the recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting variation of this was reported in which multiple (8)(9)(10) longitudinal myotomies (3-4 cm long) at three different circumferential sites were done [57]. At a mean follow-up of 44 months, 14/15 patients showed function comparable to IPAA except for frequent nocturnal soiling in 40%.…”
Section: Techniques Of Surgery For Ulcerative Colitismentioning
confidence: 97%
“…The implications of finding a positive association is that there may be value in performing a frozen section of the resection lines and if positive, further resection may be done to obtain microscopically disease-free margins. Retro-spective studies [10,11] have concluded that there is no value in such a practice. In our prospective study [5] in which microscopic disease was carefully characterized by grade of severity according to specific histologic features, we found no significant difference in recurrence rates between those with (categories 3 and 4) and those without (categories 1 and 2) features of Crohn's disease.…”
Section: Factors Influencing Recurrence Of Crohn's Diseasementioning
confidence: 99%